Glycolipid Metabolism Disorder in the Liver of Obese Mice Is Improved by TUDCA via the Restoration of Defective Hepatic Autophagy - Qinyue Guo; Qindong Shi; Huixia Li; Jiali Liu; Shufang Wu; Hongzhi Sun; Bo Zhou (International Journal of Endocrinology)
Objective. Tauroursodeoxycholic acid (TUDCA) has been considered an important regulator of energy metabolism in obesity. However, the mechanism underlying how TUDCA is involved in insulin resistance is not fully understood. We tested the effects of TUDCA on autophagic dysfunction in obese mice. Material and Methods. 500 mg/kg of TUDCA was injected into obese mice, and metabolic parameters, autophagy markers, and insulin signaling molecular were assessed by Western blotting and real-time PCR. Results. The TUDCA injections in the obese mice resulted in a reduced body weight gain, lower blood glucose, and improved insulin sensitivity compared with obese mice that were injected with vehicle. Meanwhile, TUDCA treatment not only reversed autophagic dysfunction and endoplasmic reticulum stress, but also improved the impaired insulin signaling in the liver of obese mice. Additionally, the same results obtained with TUDCA were evident in obese mice treated with the adenoviral Atg7. Conclusions. We found that TUDCA reversed abnormal autophagy, reduced ER stress, and restored insulin sensitivity in the liver of obese mice and that glycolipid metabolism disorder was also improved via the restoration of defective hepatic autophagy.